2020
DOI: 10.3390/met10121572
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Stainless Steel Waste Products Generated during Laser Cutting in Nitrogen Atmosphere

Abstract: Laser cutting technology is one of the basic approaches used for thermal processing of parts fabricated from almost all engineering materials. Various types of lasers are utilized in the industry with different attendant gases such as nitrogen or argon. When the laser beam interacts with a metal surface, the area underneath is heated to the melting point. This liquid or vaporized metal is ejected from the kerf area to the surrounding atmosphere by attendant gas and becomes undesirable waste in the form of powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…The majority of current experimental studies are found observing the morphology of cutting kerf [10][11][12], which limits the ability to reveal the physical mechanism of ejected particles. To get more appropriate results, some studies have tried to either directly track the generation of particles using a CCD camera [13] or collect and characterize the ejected particles in both open [14,15] and enclosed [9] environments. Through the CCD camera, Yilbas et al [13] found that the ejected steel particles are generally spherical with diameters ranging from 50 µm to 300 µm, where the particle size increases with higher laser power or lower assist gas velocity.…”
Section: 𝑺 𝑟𝑒𝑐𝑜𝑖𝑙mentioning
confidence: 99%
“…The majority of current experimental studies are found observing the morphology of cutting kerf [10][11][12], which limits the ability to reveal the physical mechanism of ejected particles. To get more appropriate results, some studies have tried to either directly track the generation of particles using a CCD camera [13] or collect and characterize the ejected particles in both open [14,15] and enclosed [9] environments. Through the CCD camera, Yilbas et al [13] found that the ejected steel particles are generally spherical with diameters ranging from 50 µm to 300 µm, where the particle size increases with higher laser power or lower assist gas velocity.…”
Section: 𝑺 𝑟𝑒𝑐𝑜𝑖𝑙mentioning
confidence: 99%
“…The higher the nitrogen pres-sure, the more the cutting parameters and properties can deviate from the optimal ones, yet a burr-free quality cut can still be obtained (Figure 2). Higher nitrogen pres-sure also allows for faster-cutting speed, but cutting with nitrogen at lower pressure is more cost-effective [5]. Compared to nitrogen cutting, it is 3 to 5 times slower.…”
Section: Parameters and Properties Of Cutting With Auxiliary Gasesmentioning
confidence: 99%
“…Before proceeding with laser cutting, it is very important to check the laser beam position and adjust it to the center of the nozzle (Figure 1). Failure to do so may result in poor cuts, uncut workpieces, or in damaged fiber laser parts [4][5][6].…”
Section: Introduction To Cutting Parametersmentioning
confidence: 99%
“…The process is more complicated in the case of thermal cutting due to the low melting point. It is recommended to use a high speed and optimum laser power, suitable for the thickness, in order to obtain low surface roughness [35][36][37][38][39]. Taking into account the above literature data, it can be concluded that cutting speed and auxiliary gas pressure are the most significant parameters affecting the change in surface porosity, while the impact of laser power is much less [40][41][42].…”
Section: Introductionmentioning
confidence: 99%